Pola Pertumbuhan Rumput Laut Yang Menggunakan Kantong Dan Tanpa Kantong Di Perairan Pantai Kutuh, Badung, Bali - Ayu Putu Wiweka Krisna Dewi; Endang Wulandari Suryaningtyas (Fakultas Kelautan dan Perikanan Universitas Udayana, 2020)
Seaweed farmers on Kutuh Beach experienced problems in seaweed cultivation activities, namely that seaweed cannot grow well. This is due to the large number of predators that ate seaweed in the cultivated area. One method that can be used to overcome this problem was using bags in seaweed cultivation. The purpose of the research that was carried out in July-October 2018 was to determine the effect of using bags on seaweed cultivation in Kutuh Beach waters. The method used in this research was experimental using two treatments (planting seaweed using bags and without bags) and three replications. Water quality parameters measured as supporting data ware DO, pH, salinity, temperature, nitrate, and phosphate. The result of this study was the growth of seaweed cultivated using bags is better than the growth of seaweed cultivated without bags.